The role of patients in the governance of a sustainable healthcare system: A scoping review - Monica Aggarwal; Sukhraj Gill; Adeel Siddiquei; Kristina Kokorelias; Giulio DiDiodato (PLoS ONE, 2022)
Patients, healthcare providers and insurers need a governance framework to establish the ‘rules of use’ to deliver more responsible use of services. The objective of this review was to provide an overview of frameworks and analyze the definitions of patient accountability to identify themes and potential gaps in the literature. Fifteen bibliographic databases were searched until July 2021. This included: MEDLINE, EMBASE, CINAHL, PsycINFO, SPORTDiscus, Allied and Complementary Medicine Database, Web of Science, HealthSTAR, Scopus, ABI/INFORM Global, Cochrane Library, ERIC, International Bibliography of the Social Sciences, Sociological Abstracts, Worldwide Political Science Abstracts and International Political Science Abstracts. Searches were also completed in Google Scholar. Inclusion criteria included articles focused on accountability of patients, and exclusions included articles that were not available, not written in English, with missing information, and commentaries or editorials. In total, 85530 unique abstracts were identified, and 27 articles were included based on the inclusion criteria. The results showed that patient accountability is rarely used and poorly defined. Most studies focused on what patients should be held to account for and agreed that patients should be responsible for behaviours that may contribute to adverse health outcomes. Some studies promoted a punitive approach as a mechanism of enforcement. Most studies argued for positive incentives or written agreements and contracts. While many studies recognized the value of patient accountability frameworks, there was a concern that these frameworks could further exacerbate existing socioeconomic disparities and contribute to poor health-related behaviours and outcomes (e.g., stigmatizing marginalized groups). Shared models of accountability between patients and healthcare providers or patients and communities were preferred. Before committing to a patient accountability framework for improving patient health and sustaining a healthcare system, the concept must be acceptable and reasonable to patients, providers, and society as a whole.